Marek's Disease Virus and Reticuloendotheliosis Virus Coinfection Enhances Viral Replication and Alters Cellular Protein Profiles - Du, Xusheng; Zhou, Defang; Zhou, Jing; Xue, Jingwen; Cheng, Ziqiang (Frontiers in Veterinary Science, 2022)
Co-infection with Marek’s disease virus (MDV) and reticuloendotheliosis virus (REV) causing synergistic pathogenic effects and serious losses to the poultry industry. However, whether there is synergism between the two viruses in viral replication and the roles of host factors in regulating MDV and REV co-infection remain elusive. In this study, we found that MDV and REV co-infection increased viral replication in co-infected cells compared single infection in limited period. Further, we explore the host cell responses to MDV and REV co-infection using Tandem Mass Tag (TMT) peptide labeling coupled with LC-MS/MS. Compared with MDV/REV infected cells, 38 proteins increased (fold change > 1.2) and 60 decreased (fold change <0.83) their abundance in MDV and REV co-infected cells. Differentially accumulated proteins (DAPs) were involved in important biological processes involved in immune system process, cell adhesion and migration, cellular processes, and multicellular organismal systems. STRING analysis that IRF7, MX1, TIMP3, AKT1 may be associated with MDV and REV synergistic replication in CEFs. Western blotting analysis showed that the selected DAPs were identical to the quantitative proteomics data. Taken together, we verified MDV and REV can synergistically replicate in co-infected cells, and revealed the host molecules involved it. However, the synergistic pathogenesis of MDV and REV need to be further studied.